Blinded randomised controlled trial of low-dose Adjuvant Steroids in Adults admitted to hospital with Pandemic influenza (ASAP): a trial 'in hibernation', ready for rapid activation - Lim, Wei Shen; Brittain, Clare; Duley, Lelia; Edwards, Sheila; Gordon, Stephen; Montgomery, Alan; Nguyen-Van-Tam, Jonathan; Read, Robert; Whitham, Diane; Whynes, David; Woodhead, Mark; Wootton, Dan (NIHR Health Technology Assessment Programme, 2015)
Background: There are no completed randomised trials of the use of corticosteroids in patients with severe influenza infection. Corticosteroid use in influenza is widespread, non-systematic and marked by controversy. A recent meta-analysis of observational studies of adjuvant corticosteroids in influenza found an association with increased mortality but there were important concerns regarding the risks of bias. Objectives: To (1) evaluate whether or not low-dose corticosteroids given as an adjunct to standard treatment is beneficial in patients who are hospitalised with severe pandemic influenza and (2) develop an 'off-the-shelf' clinical trial that is ready to be activated in a future pandemic. Design: Multicentre, pragmatic, blinded, randomised placebo-controlled trial. Setting: Thirty to 40 hospitals in the UK. Participants: Adults (>/= 16 years) admitted to hospital with an influenza-like illness during a pandemic. INTERVENTION: Five-day course of dexamethasone (Dexsol(R), Rosemont Pharmaceuticals Ltd) 6 mg daily, started within 24 hours of admission. Main outcome measure: Admission to Intensive Care Unit, or death, within 30 days of admission to hospital. Results: This trial has not yet been activated. It is currently set up with full ethics and regulatory approvals in place, ready for rapid activation at the onset of the next pandemic. Hurdles to setting up a pandemic trial include planning for pandemic-level pressures on UK NHS resources and co-enrolment of patients to multiple pandemic studies, ensuring adequate geographical distribution of participating sites, maintaining long-term low-level engagement with site investigators, addressing future trial-specific training needs of local investigators and resilience planning in trial management. Identified threats to trial delivery include changes to research capabilities or policies during the hibernation phase, lack of staff resources during a pandemic and the influence of media at the time of a pandemic. A mismatch in the approach to informed consent required by current regulations to that preferred by patients and the public was identified. Conclusions: This study demonstrates that advance set-up of a trial to be conducted during a pandemic, with full regulatory approvals in place, is possible. Regular review during the hibernation phase will be required. This study serves as a model for the development of other 'off-the-shelf' trials as part of preparedness planning for public health emergencies. Trial registration: Current Controlled Trials ISRCTN72331452. European Union Drug Regulating Authorities Clinical Trials number: 2013-001051-12. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 19, No. 16. See the NIHR Journals Library website for further project information.